Adaptive radiotherapy for advanced lung cancer ensures target coverage and decreases lung dose. Issue 1 (October 2016) - Møller, Ditte Sloth; Holt, Marianne Ingerslev; Alber, Markus; Tvilum, Marie; Khalil, Azza Ahmed; Knap, Marianne Marquard; Hoffmann, Lone
Abstract: Background and purpose: Advanced lung cancer patients experience anatomical changes during radiotherapy. Uncorrected, these may lead to lower tumor dose, but can be corrected for by adaptive radiotherapy (ART). Material and methods: Anatomical changes in 233 patients were monitored online on cone-beam CT-scans used for daily soft-tissue matching. If systematic changes above the pre-defined trigger criteria were observed, a new CT-scan, delineations, and treatment plan were made, restoring the intended dose distribution. Dose distributions with and without adaptation were compared. The first fifty ART patients were given two surveillance CT-scans during radiotherapy. These were used to evaluate delivered dose for patients without adaptation. The first fifty-two patients treated with ART were also compared with 52 pre-ART patients to evaluate the reduction in normal tissue doses. Results: Sixty-three patients (27%) were adapted. Seventy-five per cent of all adaptations correctly adjusted for a decrease in tumor dose. Eighty-seven surveillance CT-scans were obtained for the first fifty patients and in only 2% of the cases, a decrease in tumor coverage (ΔV95%CTV > 1%) was observed. With ART we observed a significant decrease in lung dose (MLD reduced from 14.6 Gy to 12.6 Gy on average). Conclusions: Implementation of soft-tissue match combined with ART decreased the lung dose. The trigger criteria used correctly identified all but one (98%) of the patients requiring adaptation with a false positive rate of 20%.